Respiratory viruses in pediatric emergency department patients and their family members. Issue 1 (30th July 2020) - Matienzo, Nelsa; Youssef, Mariam M.; Comito, Devon; Lane, Benjamin; Ligon, Chanel; Morita, Haruka; Winchester, Arianna; Decker, Mary E.; Dayan, Peter; Shopsin, Bo; Shaman, Jeffrey
Abstract: Background: Respiratory viral infections account for a substantial fraction of pediatric emergency department (ED) visits. We examined the epidemiological patterns of seven common respiratory viruses in children presenting to EDs with influenza‐like illness (ILI). Additionally, we examined the co‐occurrence of viral infections in the accompanying adults and risk factors associated with the acquisition of these viruses. Methods: Nasopharyngeal swab were collected from children seeking medical care for ILI and their accompanying adults (Total N = 1315). Study sites included New York Presbyterian, Bellevue, and Tisch hospitals in New York City. PCR using a respiratory viral panel was conducted, and data on symptoms and medical history were collected. Results: Respiratory viruses were detected in 399 children (62.25%) and 118 (17.5%) accompanying adults. The most frequent pathogen detected was human rhinovirus (HRV) (28.81%). Co‐infection rates were 14.79% in children and 8.47% in adults. Respiratory syncytial virus (RSV) and parainfluenza infections occurred more often in younger children. Influenza and HRV occurred more often in older children. Influenza and coronavirus were mostly isolated in winter and spring, RSV in fall and winter and HRV in fall and spring. Children with HRV were more likely to have history of asthma. Adults with the same virus as their child often accompanied ≤ 2‐year‐old‐positive children and were more likely to be symptomatic compared to adults with different viruses. Conclusions: Respiratory viruses, while presenting the same suite of symptoms, possess distinct seasonal cycles and affect individuals differently based on a number of identifiable factors, including age and history of asthma.